Productivity and nutrition of castor bean fertilized with sewage sludge stabilized by different processes (Research, Society and Development, 2022)
The objective of this study was to evaluate production in castor bean crop treated with sewage sludge (SS) subjected to different stabilization processes. The experiment was conducted in a Cambisol, with a randomized block design, in subdivided plots, with four replications and six main treatments: without fertilization; fertilization with solarized, composted, vermicomposted, or limed SS; and mineral fertilizer. The secondary treatment was soil depth or plant part. Soil and plant attributes were evaluated by comparing the treatments using the Scott–Knott test (P ≤ 0.05). The fertilization with limed SS resulted in a greater increase in soil fertility-related attributes than with the other fertilizers. The fertilizations increased the P, K, Ca, Mg, and S levels; pH; sum of bases; cation exchange capacity; and the percentage of exchangeable bases in the upper soil layer in comparison to that in the lower layer; however, in general, there was no influence on nutrient content in the plant. Regardless of the stabilization process, fertilization with SS generated castor bean seed yields ranging from 2.56 to 3.02 t ha-1, similar to that with mineral fertilization and higher than that of unfertilized soil.